Development Of Website and Moodle Learning Management Systems at a YPPI-II High School - Darmanto, Darmanto; Prayitno, Agus; Hermawan, Budi (KnE Social Sciences, 2023)
In the midst of the Covid-19 pandemic, school management continues to strive to maintain the quality of academic services so that Teaching and Learning Process (TLP) activities always run as they should. However, there are some barriers to TLP with the Distance Learning (DL) pattern, either from the preparative aspect of Human Resources (HR) or network technical aspects. Also, the partner schools do not yet have the official website facilities and significant DL media. Meanwhile, Information and Communication Technology (ICT) is currently the main medium to reach students in DL. Teachers need to reconsider when, where, and how online learning occurs, and adapt their methodological approach. Therefore, through the Community Partnership Program (CPP), the implementation team offers the development of a school website and the use of a Moodle-based Learning Management System (LMS) in partner schools at SMA YPPI-II Surabaya. This community service activity is done to support the website as a medium of information and promotion and to maintain an efficient and effective existence. Likewise, the Moodle application is used as a support for online TLP in addition to direct learning through video conference with the digital platform, like Zoom or Google meets. The method of implementing CPP is by presenting, training, and mentoring the Moodle application and website for teachers and partner staff who will later act as users. The results of this activity made a positive contribution to the improvement of HR skills and access to school information with the related parties. Keywords: distance learning, community partnership program, learning management system, Moodle